PERANCANGAN ULANG INOVASI KLOSET DUDUK MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT - Abi Mael Sihombing; Diaz Arjun Annolu; Sumantri Safitra; Fadhil Zaky Ikhwani (LPPM Universitas Bina Bangsa, 2022)
The toilet is a facility whose main use is as a place to dispose of waste. Apart from being a place to dispose of waste, the toilet can also be used as a place to clean the body. One form of infrastructure in the toilet is a toilet, the toilet itself has a function as a place to dispose of human waste such as defecating and urinating. Toilets also have various types and sizes, some are used in a sitting state and used in a squatting state. The shape and suitability of the toilet is also very influential on health. Where the level of risk of someone contracting a disease attached to the toilet seat is higher because the use of the toilet seat is in direct contact with the Gluteus body part. Based on these conditions, a redesign of the toilet seat will be carried out, in order to meet the appropriate criteria. The design is in the form of adding UV Light which functions as a sterilizer for the interior that is exposed to dirt. The method used is Quality Function Deployment, namely product development that is well known in the industrial world. From the results of the analysis that has been carried out, it is known that the condition of the toilet seat after the redesign is better than the previous design